2015
DOI: 10.5812/numonthly.26847
|View full text |Cite
|
Sign up to set email alerts
|

Dialysate With High Dissolved Hydrogen Facilitates Dissociation of Indoxyl Sulfate From Albumin

Abstract: Background:Protein-bound toxins such as indoxyl sulfate (IS) are not efficiently removed by conventional hemodialysis (HD).Objectives:To improve the removal of IS, we performed an in vitro study to evaluate the effects of high dissolved hydrogen on the dissociation of IS from albumin using simulated HD.Materials and Methods:Wasted dialysate from peritoneal dialysis was concentrated a hundred times using extracorporeal ultrafiltration method. Dialysate with high dissolved hydrogen was made by mixing concentrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 20 publications
(17 reference statements)
0
3
0
Order By: Relevance
“…The initial report by Huang et al demonstrated a reduction in inflammatory markers in hemodialysis using electrolyzed water [96,97]. Furthermore, it was reported that ERW enhances dissociation of indoxyl sulfate from albumin as an underlying mechanism [98]. However, widespread recognition of this treatment system did not occur.…”
Section: Clinical Studies Using Ehw For Hemodialysismentioning
confidence: 99%
“…The initial report by Huang et al demonstrated a reduction in inflammatory markers in hemodialysis using electrolyzed water [96,97]. Furthermore, it was reported that ERW enhances dissociation of indoxyl sulfate from albumin as an underlying mechanism [98]. However, widespread recognition of this treatment system did not occur.…”
Section: Clinical Studies Using Ehw For Hemodialysismentioning
confidence: 99%
“…Moreover, high sodium concentrations in the substituate of predilution HDF at increased plasma ionic strength could improve PBUT removal ( Krieter et al, 2017 ). In addition, some studies have found that the use of high dissolved hydrogen dialysate can promote the dissociation of IS from the albumin binding site, increase the level of free IS and improving the scavenging effect of IS in the filtrate ( Tange et al, 2015 ).…”
Section: Metabolism and Elimination Of Uremic Toxinsmentioning
confidence: 99%
“…Another area of research concerns altering the dialysis milieu in order to affect the binding of URS to plasma proteins. Examples of this effort which have data supporting their use include using hypertonic solution, the use of albumin-binding site competitors such as tryptophan and docosahexaenoic acid, increasing temperature, plasma dilutions, and pH manipulation of the dialysate [47,[90][91][92][93][94].…”
Section: Dialysismentioning
confidence: 99%